2022
DOI: 10.4081/dr.2022.9512
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between poor skin disorders prognosis and serum zinc level: A narrative review

Abstract: Zinc is a trace nutrient essential for the normal growth and development of human body. The main aim was to evaluate the significant association between measured zinc status in relation to different skin disorders and their severity. PubMed®, Google® Scholar™ and Cochrane© Reviews databases were searched for studies from January 2017 to June 2021, using the terms; zinc serum levels, zinc plasma levels and different dermatosis in the review, only human studies in English language were reviewed and the studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
1
1
0
Order By: Relevance
“…This observed rise in plasma Zn levels can reasonably be attributed to the stimulation of MTs by ITR, thereby promoting the release of Zn into the bloodstream. There are only several studies supporting the effectiveness of oral Zn supplementation in reducing AV severity and sebum secretion [29,35]. In light of these supportive findings and the distinctive outcomes of this study, it is plausible to suggest that ITR reduces AV symptoms by increasing plasma Zn levels through the stimulation of MTs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This observed rise in plasma Zn levels can reasonably be attributed to the stimulation of MTs by ITR, thereby promoting the release of Zn into the bloodstream. There are only several studies supporting the effectiveness of oral Zn supplementation in reducing AV severity and sebum secretion [29,35]. In light of these supportive findings and the distinctive outcomes of this study, it is plausible to suggest that ITR reduces AV symptoms by increasing plasma Zn levels through the stimulation of MTs.…”
Section: Discussionsupporting
confidence: 60%
“…However, the existing literature presents conflicting results. Notably, four studies have suggested significant differences in serum Zn levels between individuals with AV and healthy [11,[29][30][31]. Conversely, a controlled study encompassing a cohort of 200 patients failed to establish any substantial correlation between Zn levels and the occurrence or severity of AV [32].…”
Section: Discussionmentioning
confidence: 99%